Evaluation of Left Ventricular Function in Diabetic Patients: Insights from Dipyridamole-induced Heart Rate Variability and G-SPECT Imaging Techniques - Nafisi, Marieh; Farzipour, Soghra; Gholami-Chaboki, Bahare; Mousavi, Seyed Mehdi; Baharvand, Fatemeh; Souri, Zobin; Savarrakhsh, Amir; Zefrei, Fatemeh Jalali (Current Hypertension Reviews, 2025)
IntroductionLeft Ventricular Dysfunction (LVD) is a frequent complication in Diabetes mellitus (DM) patients, often worsened by cardiovascular disease. This study explores the role of dipyridamole (DP)-induced heart rate variability and G-SPECT imaging in evaluating LVD in DM patients. This study aimed to evaluate the relationship between heart rate ratio (HRR) during DP stress and LVD parameters derived from gated SPECT (G-SPECT) in DM patients, aiming to identify if HRR can serve as a marker for early LVD assessment.MethodsA cross-sectional study of 125 patients referred for cardiac scanning. Patients were grouped by diabetic status and HRR (≤ 1.2 vs. > 1.2) post-DP. G-SPECT-derived left ventricular parameters were compared between groups.ResultsG-SPECT showed that peak filling rate (PFR) was higher in non-DM patients. In the HRR ≤ 1.2 group, DM patients had significantly higher end-diastolic volume (EDV) and end-systolic volume (ESV) than non-DM patients (EDV: 66.41±31 vs. 51.34±18, p-value:0.009; ESV: 27.88±11.21 vs. 18.63±15.5, p- p-value: 0.015).DiscussionThis study evaluated the role of heart rate response during dipyridamole stress testing combined with G-SPECT imaging in assessing left ventricular dysfunction (LVD) in diabetic patients. The findings indicate that changes in ventricular volume parameters, along with heart rate response, may serve as early markers of cardiac impairment, potentially facilitating earlier detection and improved management of cardiac complications in this population.ConclusionReduced HRR during DP stress, combined with G-SPECT, may aid in the assessment of LVD in DM patients, potentially facilitating earlier diagnostic insights.
Keywords: left ventricular functional parameters